PEMANFAATAN TEKNOLOGI INFORMASI DALAM MONITORING PROGRAM CORPORATE CULTURE PURPOSE (CCP) UNTUK MEWUJUDKAN BUDAYA KERJA ZERO ACCIDENT DI PT PLN UID S2JB - Resa Ayu Sari; Aminullah Imal Alfresi (Jurnal Riset Sistem Informasi, 2025)
This study examines the use of information technology in monitoring the Corporate Culture Purpose (CCP) program at PT PLN (Persero) UID S2JB to support a Zero Accident work culture. A mixed-methods approach was applied through observation, interviews, documentation, and data analysis using the Team Gaint application. Results show that most units achieved a medium compliance level (60–80%), with 71% of programs meeting standards and 29% not compliant. The main challenges include reporting delays, limited internet access, and insufficient digital training. The use of Team Gaint has proven effective in accelerating monitoring, although improvements in infrastructure and human resource competence are still required.